Evaluación del abono orgánico humus, en el establecimiento del pasto King Grass Morado (Pennisetum purpureum x Pennisetum typhoides) en la Quinta Experimental Punzara-UNL. - Pesantez Ordoñez, Alison Mayeli (2025)
This research was conducted to evaluate the effect of organic humus fertilizer on the establishment of King Grass Morado (Pennisetum purpureum x Pennisetum typhoides) at the Punzara-UNL Experimental Farm. An experimental design with randomized blocks was used. The research area of 1500m2 consisted of three plots, each plot with two divisions: a control area and a treatment area, with two phases, field and laboratory. Organic humus fertilizer was used in the randomized treatments. The objective was to evaluate variables: germination, plant height, number of leaves, survival, and biomass production. The results regarding germination showed a significant statistical difference, with a greater increase in the humus treatment at 62.00%, compared to the control treatment at 43.89%. In the plant height variable, a greater increase was recorded at 120 days with an average of 153 cm, while at 60 days an average of 87 cm was recorded. In the number of leaves, it was noted that there was no statistical difference, with the humus treatment having 10.43 leaves/plant, while the control treatment had 10.15 leaves/plant. Regarding the survival variable, the result was 100%. Biomass production showed a higher production in the control treatment with an average of 52.92 t/ha. In the nutritional composition, no statistically significant results were detected. It is concluded that the use of organic fertilizers, especially humus, potentially increases the germination rate by creating a more favorable environment for the initial growth of seedlings.